A Simple Oral Controlled Release Device that Releases Drug via Zero Order Kinetics (The East and Central African Journal of Pharmaceutical Sciences, 2020)
The present study was aimed at preparing a simple device that releases drug via zero order kinetics. The basic matrix forming material employed was glycerol monosterate in combination with either methylcellulose or ethylcellulose. The drugs used to evaluate the release characteristics of the resulting matrices were aspirin and propranolol hydrochloride. Drug release from glycerol monostearate and metheylcellulose and from glycerol monosterate and ethylcellulose matrices was best explained by zero order kinetics. The matrices were easily prepared via direct compression after lubrication of the die and punches. Such zero order release oral devices can be used to deliver drug at a predetermined constant rate that will result in constant drug levels in the body for prolonged periods of time.
Keywords: Device, Controlled, Drug, Release, Kinetics.